Analysis and optimisation of a rib-stiffened vaulted floor for dynamic performance. (15th June 2020) - Wu, H.; Liew, A.; Van Mele, T.; Block, P.
Highlights: Rib-stiffened vaulted floors can have high natural frequencies and low modal masses. However it is shown here that they can still show general sensitivity to vibration. Relationships between geometric/modal parameters and dynamic performance were found. Mass distribution by manual/automated optimisation can improve dynamic performance. This research allows for the dynamic assessment and optimisation of vaulted floors. Particularly where high natural frequencies are created by removing structural mass. Abstract: There appears in the construction of modern multi-storey buildings in recent years, a prevailing trend for large bay sizes, lightweight floor systems and reduced dividing partitions. These tendencies have aroused a greater awareness of potential vibration problems when the structural floor systems are subjected to human induced activities such as footfall loading, as vibration performance may become an influential factor in the design of lightweight floor structures. A rib-stiffened vaulted floor described in this paper, can achieve sufficient structural stiffness and load-bearing capacity in an ultra-lightweight construction system. The aim of this study was to obtain a fundamental understanding of the floor's dynamic behaviour and to develop appropriate measures to improve its dynamic performance. Dynamic analyses and assessment were conducted on 180 mesh models of the floor with different combinations of geometric parameters and compared against acceleration acceptance criterion. After the parametric performance evaluations, qualitative and quantitative relationships among the geometric parameters, modal parameters and dynamic performance were found, where it was shown that most floors failed to meet the acceptance criterion. Different approaches were then taken to improve the dynamic performance of the floors, using manual distribution of additional mass or optimised relocation of constant total mass. Selective distribution of mass in targeted areas accomplished considerable improvements in the dynamic performance. This paper identifies that statically optimised low-mass floors may be particularly sensitive to footfall loading, and establishes a reliable procedure for dynamic analysis using the dynamic characteristics of a rib-stiffened vaulted floor, revealing improvements to dynamic performance and providing insight into high frequency floors.